2018
DOI: 10.1177/0023677218771720
|View full text |Cite
|
Sign up to set email alerts
|

Diurnally active rodents for laboratory research

Abstract: Although inbred domesticated strains of rats and mice serve as traditional mammalian animal models in biomedical research, the nocturnal habits of these rodents make them inappropriate for research that requires a model with human-like diurnal activity rhythms. We conducted a literature review and recorded locomotor activity data from four rodent species that are generally considered to be diurnally active, the Mongolian gerbil ( Meriones unguiculatus), the degu ( Octodon degus), the African (Nile) grass rat (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Conversely, as seen in other rodents (Krubitzer et al, 1986; Brett-Green et al, 2004), it can be speculated that there are no additional secondary somatosensory areas besides S2 in this species. Though the agouti has a brain considerably larger than the rat’s, the smaller number of somatosensory cortical areas in the former may be associated with adaptations to a diurnal lifestyle (Divac, 1995), as seen in diurnal caviomorphs such as guinea pig and degu (Grant et al, 2017; Refinetti and Kenagy, 2018), and also in nocturnal non-caviomorphs (Campi and Krubitzer, 2010). Similar to another diurnal rodent, the squirrel, the agouti has a larger proportion of its dorsolateral cortex devoted to visual areas when compared to nocturnal rodents such as the rat (Picanço-Diniz et al, 1989; Campi and Krubitzer, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, as seen in other rodents (Krubitzer et al, 1986; Brett-Green et al, 2004), it can be speculated that there are no additional secondary somatosensory areas besides S2 in this species. Though the agouti has a brain considerably larger than the rat’s, the smaller number of somatosensory cortical areas in the former may be associated with adaptations to a diurnal lifestyle (Divac, 1995), as seen in diurnal caviomorphs such as guinea pig and degu (Grant et al, 2017; Refinetti and Kenagy, 2018), and also in nocturnal non-caviomorphs (Campi and Krubitzer, 2010). Similar to another diurnal rodent, the squirrel, the agouti has a larger proportion of its dorsolateral cortex devoted to visual areas when compared to nocturnal rodents such as the rat (Picanço-Diniz et al, 1989; Campi and Krubitzer, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we document individual variation in time of daily activity onset in a laboratory population of 52 antelope ground squirrels, Ammospermophilus leucurus, a species that we have previously shown to be an excellent diurnal rodent model, more reliably diurnal than the Mongolian gerbil, the degu, and the Nile grass rat [56]. Our measurements allow us to chronotype the individuals and assess further relationships between the range of chronotypes and other parameters of circadian rhythmicity.…”
Section: Introductionmentioning
confidence: 81%
“…Ideally, such an investigation should be conducted with human participants; however, because of the long time in isolation required of subjects in these types of study, it is important to first conduct studies in animal models to determine whether studies in humans are justified. We chose antelope ground squirrels (Ammospermophilus leucurus) as an animal model because this species is consistently and virtually exclusively diurnal, has very robust activity rhythms, exhibits a chronotype distribution as wide as that of humans, has a mean free-running period similar to that of humans, and is easily housed in the laboratory [56]. In human studies, which are predominantly based on surveys rather than actual activity records, it has been suggested that chronotype could be defined as the time of mid-sleep on free (non-working) days [13].…”
Section: Rationalementioning
confidence: 99%
“…Circadian rhythmicity exists in almost every biological process, and many animals display obvious differences in physiology between day and night. Unfortunately, the animals used most widely laboratory in biomedical research—rats, mice, guinea pigs, rabbits, etc.—are nocturnal (active at night) . As we all know, humans are diurnal (active during the day), so researchers should consider the importance of time of day in their experimental procedure designs, and a diurnal animal model would be more suitable for some experiments than the traditional nocturnal models.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent reports confirmed that gerbils are diurnal, and they have also been identified as ideal laboratory animals in neurological and pathological research . However, more recent studies have indicated that the activity rhythms of the gerbil are weaker than those of other two diurnal animals, the antelope ground squirrel and the African grass rat . Thus, there is a need to confirm the suitability of the gerbil as a diurnal laboratory animal model.…”
Section: Introductionmentioning
confidence: 99%